FINANCIAL GOVERNANCE TRAINING TO IMPROVE FINANCIAL PERFORMANCE FOR PRINTING BUSINESS ACTORS - Agung Wijaya; Fitra Ria Silvida; Tito Malindo (Pedagogic Research-Applied Literacy Journal, 2024)
This community service activity aims to increase the understanding and skills of Brangkal printing business actors in financial management. Through this training, business actors are expected to be able to manage their finances more effectively and efficiently, which in turn will improve the performance and sustainability of their business. The methods used in this training include material delivery, interactive discussions, and direct practice. The training material includes the basics of accounting, cash flow management, preparation of financial reports, and financial planning strategies. The results of this training show a significant increase in participants' understanding and ability to manage business finances. Participants also reported positive changes in the way they recorded and planned their finances, which resulted in increased operational efficiency and profitability of their businesses. Discussions in this training identified several challenges faced by business actors in implementing good financial governance, including limited resources and previous knowledge. However, through this training, business actors obtain practical solutions and support to overcome these challenges.